2022
DOI: 10.3389/fonc.2022.971959
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing anti-tumour innate immunity by targeting the DNA damage response and pattern recognition receptors in combination with radiotherapy

Abstract: Radiotherapy is one of the most effective and frequently used treatments for a wide range of cancers. In addition to its direct anti-cancer cytotoxic effects, ionising radiation can augment the anti-tumour immune response by triggering pro-inflammatory signals, DNA damage-induced immunogenic cell death and innate immune activation. Anti-tumour innate immunity can result from recruitment and stimulation of dendritic cells (DCs) which leads to tumour-specific adaptive T-cell priming and immunostimulatory cell in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 313 publications
0
12
0
Order By: Relevance
“…Next, the expression of cell cycle checkpoint markers was studied to elucidate if 4T1 cells could effectively initiate DNA damage repair response ( Chan Wah Hak et al, 2022 ). The results showed that at a lower dose of Bi-212-MAA, there was increased activation of cell cycle checkpoint markers Chk1, Chk2, and Wee1; however, at higher dose levels, Chk1, Chk2, and Wee1 activation were comparable to control ( Figure 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…Next, the expression of cell cycle checkpoint markers was studied to elucidate if 4T1 cells could effectively initiate DNA damage repair response ( Chan Wah Hak et al, 2022 ). The results showed that at a lower dose of Bi-212-MAA, there was increased activation of cell cycle checkpoint markers Chk1, Chk2, and Wee1; however, at higher dose levels, Chk1, Chk2, and Wee1 activation were comparable to control ( Figure 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, analogous to the combination studies with radiotherapy, long-lasting antitumor immunity was also observed in a murine colorectal model when ATR inhibition was combined with anti-PD-L1 antibodies and platinum-based chemotherapy ( 52 ). Promising preclinical results have led to several ongoing early-phase clinical trials with immune checkpoint blockade in combination with ATR inhibitors, and at least one of these studies addresses the triple-treatment with radiotherapy [reviewed in ( 11 , 53 )]. Of note is that even the co-treatment of radiotherapy and immune checkpoint blockade is far from fully developed.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent preclinical studies suggest that ATR inhibition can increase the immunostimulatory effects of radiotherapy. This has been demonstrated in multiple murine models in vivo , where ATR inhibition combined with irradiation caused activation of CD8 + T cells, dendritic cells and natural killer cells, induction of immunological memory and less regulatory T cell-mediated immunosuppression ( 11 , 19 21 ). Nevertheless, the underlying molecular mechanisms are incompletely understood.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Combining therapy with existing therapies such as immune checkpoint inhibitors still poses numerous challenges. 134 There is a need to maximize the immunestimulatory effects of radioimmunotherapy. 135 CBTH is a strong candidate for wider dissemination and implementation in the cancer population.…”
Section: Radiation and Immunotherapymentioning
confidence: 99%